Spatial equalization of selected sound source by digital inverse filtering - Ciesielka, Wojciech (Archives of Acoustics, 2007)
The article presents digital inverse equalizers, enabling active sound control by means of directional characteristics equalization of selected sound source. Theoretical grounds of these systems are based on inverse filtration theory. Mathematical model of the equalizer, as well as experimental results confirming effectiveness of its operation have also been described in the study, which presents directional characteristics of Visaton BG17 loudspeaker, and its selected impulse responses prior to, and after equalization.